CHINA COERCIVE DIPLOMACY THROUGH SOUTH CHINA SEA CONFLICT AND BELT & ROAD INITIATIVES - Pitra, Haetami (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
This paper studies Chinese coercive diplomacy by first analyzing the South China Sea (SCS) issue from the perspective of China national interest which has Belt & Road Initiatives (BRI) political agenda (formerly known as OBOR). Through BRI, China will be a counterweight to the world economic power in countering US hegemony. This paper aims to describe the coercive form of China diplomacy which has been implemented through both phenomena and to analyze China coercive diplomacy using theory and relevant concept. To achieve those goals, this paper employs qualitative research method as well as national interest and neorealism theory. The findings of this paper suggest that, in reflection of China-Sri Lanka bilateral experience, BRI is one of debt-track diplomacy of China commodities in maintaining energy and economy security. This paper is expected to be one of the studies about South China Sea which can see BRI more in the opportunities it brings